Investigating thermal performance of combined use of SiO2-water nanofluid and newly designed conical wire inserts - Oflaz, Fatma; Keklikcioglu, Orhan; Ozceyhan, Veysel (Elsevier, 2022)
Background: The combined use of augmentation methods plays a significant role to enhance the thermohydraulic performance of thermal systems. This experimental study explores the thermohydraulic performance of a heat exchanger tube with the combined use of SiO2-water nano-fluids and newly designed conical wire inserts. Methods: In this study, a new wire coil insert with different properties from those previously proposed was created. The newly designed inserts were placed in a tube at five distances ranging from 0 to 33.6 mm and SiO2-water nanofluids were used at four volume concentrations (0.5-1.25%). The two step method was used to prepare nanofluids and the experiments were conducted in turbulent flow.Significant findings: The highest heat transfer performance was obtained in the conical wire inserts with pitch ratio of 0, and the least friction loss was obtained in the conical wire inserts with pitch ratio of 4. The best Performance Evaluation criteria was 1.75 at Reynolds number of 3338 and volume concentration of 1.25% for conical wire inserts with pitch ratio of 0. Moreover, the use of nanofluids provided a remarkable heat transfer rate with increased Reynolds number at high volume concentrations, whereas nanofluids at low volume concentrations slightly affected the heat transfer rate and pressure drop. The combination of two techniques presented a promising option for improving the hydrothermal qualities of the heat exchanger.
Keywords: Conical wire inserts; Pressure drop; Heat transfer enhancement; Performance evaluation criteria; Nanofluids